Hydrotalcite-derived multi-metal oxide, synthetic method and application thereof
Through the hydrotalcite-derived polymetal oxide catalyst, the problem of difficulty in separation and reuse of catalysts in transesterification method is solved, and efficient production of dimethyl carbonate is achieved, which reduces production costs and increases the recycling rate of the catalyst.
Patent Information
- Application Number
- CN202411072376.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-20
AI Technical Summary
In the existing dimethyl carbonate production process, the transesterification method uses a large amount of sodium methoxide catalyst, high production cost, difficult to separate and reuse the catalyst, and a single metal oxide catalyst is prone to deactivate.
The Mg2ZrxZn-LDH precursor was prepared by reacting zinc nitrate, magnesium nitrate, zirconium nitrate, sodium carbonate and sodium hydroxide with hydrotalcite, and calcined under specific conditions to prepare the polymetal composite oxide. Catalyst for transesterification reaction of propylene carbonate and methanol.
The multiple recycling of catalysts has been achieved, which significantly improves the single-pass and multiple utilization yield of dimethyl carbonate, reduces production costs, and does not generate solid waste in the catalytic process, which is green and efficient.
Smart Images

Figure CN119158562A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of propylene carbonate preparation, and particularly relates to a hydrotalcite-derived multi-metal oxide, a synthesis method and application thereof. Background Art
[0002] Dimethyl carbonate (DMC) is a chemical raw material with excellent environmental performance and wide application. It is also an important organic synthesis intermediate. Its molecular structure contains functional groups such as carbonyl, methyl and methoxy groups, and has multiple reaction properties. It is safe, convenient, less polluting and easy to transport in production. In addition, dimethyl carbonate is also an excellent lithium-ion battery electrolyte that can effectively improve the battery's charge and discharge capacity and capacity density, greatly enhancing the battery's safety performance and service life. Driven by the rapid development of new energy vehicles, its preparation has received widespread attention.
[0003] The production process of dimethyl carbonate used the phosgene methanol method in the early stage, but the raw material phosgene in this method is highly toxic and seriously corrosive to equipment and pipelines. It has been replaced by other non-phosgene processes. At present, the ester exchange method is mainly used to produce dimethyl carbonate at home and abroad. The principle is to use propylene carbonate and methanol to undergo an ester exchange reaction under alkaline catalyst conditions such as sodium alcohol to generate dimethyl carbonate and alcohol by-products. Although sodium alcohol is widely used as a catalyst for ester exchange reactions, there are still common problems that need to be solved: 1. In the production process of the ester exchange method, a methanol solution of sodium methoxide is used as a catalyst, and the amount of sodium methoxide is large, and the production cost accounts for a high proportion. 2. In the process of generating dimethyl carbonate by ester exchange reaction, the by-product propylene glycol is difficult to separate from the sodium methoxide catalyst. At present, most of the catalysts are separated by hydrolysis and carbonization processes, and the generated sodium carbonate solids are deposited, affecting the normal operation of the equipment. 3. After the catalyst is converted into sodium carbonate, it loses its activity and cannot be reused. Therefore, it is urgent to find a new recyclable new solid catalyst suitable for the production of dimethyl carbonate.
[0004] In recent years, solid metal oxide alkaline catalysts such as MgO and ZnO have been widely used in transesterification reactions to synthesize DMC. However, single metal oxides such as MgO and ZnO can react with water and CO2 in the air during preparation and storage, thereby becoming inactivated. In addition, the composite oxide provided by the present invention has stronger acidity and alkalinity and a larger specific surface area than single metal oxides; it can also change the lattice structure by incorporating metal cations with different electronegativity, thereby changing the acidity and alkalinity of the catalyst surface; and its catalytic activity can be changed by changing the raw material molar ratio and preparation conditions of the catalyst, so it shows good application prospects in multiphase base catalytic reactions. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the present invention provides a hydrotalcite-derived multimetal oxide, a synthesis method and its application. The present invention uses zinc nitrate hexahydrate, magnesium nitrate hexahydrate, zirconium oxynitrate hydrate, sodium carbonate, sodium bicarbonate and pure water as raw materials, and the obtained composite metal oxide catalyst has a good catalytic effect in the process of synthesizing dimethyl carbonate from propylene carbonate and methanol. In order to achieve this purpose, the technical solution provided by the present invention is as follows:
[0006] The present invention provides a multi-metal oxide derived from hydrotalcite, which is prepared by reacting zinc nitrate, magnesium nitrate and zirconium oxynitrate as raw materials with sodium carbonate and sodium hydroxide to obtain Mg2Zr x Zn-LDH precursor; and then calcined to obtain, wherein x is 0.3 to 0.5.
[0007] The present invention also provides a method for synthesizing the multi-metal oxide, comprising the following steps:
[0008] Step 1: Preparation of Mg2Zr x Zn-LDH precursor: Dissolve zinc nitrate, magnesium nitrate and zirconium oxynitrate in water to obtain solution A; add sodium carbonate solution and sodium hydroxide solution dropwise to solution A, stir vigorously, and control the pH of the mixed solution; heat the obtained slurry, separate the obtained precipitate Mg2Zr x Zn-LDH was washed with water and dried to obtain Mg2Zr x Zn-LDH precursor;
[0009] Step 2: Synthesis of multi-metal composite oxides: Mg2Zr synthesized in step 1 x The Zn-LDH precursor is obtained by calcining at a certain heating rate to a specific temperature under a specific atmosphere.
[0010] In step 1, Zn 2+ Mg 2+ 、Zr 4+ The sum of the concentrations is 0-0.05 mol / L. Exceeding this concentration will affect the morphology of the generated substance. If the concentration is too high, the particle size will be too large and the specific surface area will be too small.
[0011] In step 1, the zinc nitrate, magnesium nitrate and zirconium oxynitrate are salts or their respective hydrates.
[0012] In step 1, the pH range of the mixed solution is 9 to 11. If the pH is too low, hydrotalcite precipitation cannot be formed, and if the pH is too high, hydroxide precipitation will be directly formed. Preferably, the pH of the mixed solution is controlled at about 10 to facilitate the formation of Mg2Zr x Zn-LDH precipitation.
[0013] In step 1, the obtained slurry is heated at 100-120°C for 8-12h; the precipitate is washed and dried at a drying temperature of 80°C.
[0014] Furthermore, in step 1, the molar ratio of Mg:Zr:Zn is 2:0.3-0.5:1, and the present invention explores the catalytic effects of different proportions of the three metals.
[0015] Furthermore, in step 1, the concentration of the sodium hydroxide solution is 1-3 mol / L, preferably 2 mol / L; the concentration of the sodium carbonate solution is 0.2-0.5 mol / L, preferably 0.3 mol / L, so as to better adjust the pH of the solution.
[0016] Furthermore, in step 2, the calcination atmosphere should be an inert gas nitrogen atmosphere or an air atmosphere.
[0017] Furthermore, in step 2, the calcination temperature is 500-900°C.
[0018] Furthermore, in step 2, the calcination heating rate is 2-5°C / min, preferably 5°C / min, so that the calcination reaction proceeds smoothly.
[0019] Furthermore, in step 2, the calcination time is 2-4 hours, so that Mg2Zr x Zn-LDH was calcined completely.
[0020] In the embodiment of the present invention, Mg2Zr x The catalysts obtained by calcining the Zn-LDH precursor at 500℃ in air and the Mg2Zr x The catalyst obtained by calcining the Zn-LDH precursor in nitrogen at 900°C is used for catalytic reaction, and the single-pass yield of dimethyl carbonate is significantly higher than that under other conditions. At the same time, the yield of dimethyl carbonate is still relatively high when the catalyst is used for the second and third times, thus realizing the multiple recycling of the catalyst.
[0021] The present invention also provides the use of the multi-metal oxide in catalyzing the transesterification reaction of propylene carbonate and methanol.
[0022] The present invention synthesizes a multi-metal composite oxide catalyst based on a hydrotalcite-like precursor by a two-step method and uses it to catalyze the transesterification reaction of propylene carbonate and methanol, showing a catalytic activity superior to that of the sodium methoxide catalyst used in industry, and the catalyst can be recycled three times while still maintaining a high catalytic activity. The method is simple, efficient, green, and does not generate solid waste during the catalytic process, and has important application value in the field of synthesizing dimethyl carbonate by transesterification.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention provides a method for synthesizing multi-metal oxides by using hydrotalcite precursors in a fast, simple, green and efficient manner. The method is simple to operate and has the following advantages: 1. The reaction raw materials are cheap and green and pollution-free; 2. The reaction conditions are simple, the reaction can be carried out quickly, and energy and time are saved; 3. The ester exchange reaction of propylene carbonate and methanol shows good catalytic activity; 4. The catalyst is easy to separate during the catalytic process and can be recycled. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 Mg2Zr in Example 10 0.4 Zn-LDH and Mg2Zr 0.4 XRD pattern of Zn-N-900;
[0027] Figure 2 Mg2Zr in Example 10 0.4 SEM image of Zn-N-900;
[0028] Figure 3 Mg2Zr in Example 10 0.4 Zn-LDH and Mg2Zr 0.4 Thermogravimetric curve of Zn-N-900. DETAILED DESCRIPTION
[0029] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0031] Embodiment 1:
[0032] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.3:1 was prepared by coprecipitation. 0.3Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.3:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL of deionized water to obtain.
[0033] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.3 The Zn-LDH precursor was calcined in air at 500 °C for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.3 Zn-A-500.
[0034] (2)Mg2Zr 0.3 Catalytic effect test of Zn-A-500: Propylene carbonate and methanol were added into the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.3 Zn-A-500, heated to 70℃ and kept warm for 4h. After the reaction, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 83.67%. After each reaction, the catalyst was separated from the reaction system, washed, dried, and reused as a catalyst in a new reaction system. After testing Mg2Zr 0.3 The secondary utilization dimethyl carbonate yield of Zn-A-500 was 68.26%.
[0035] Embodiment 2:
[0036] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.4:1 was prepared by coprecipitation. 0.4 Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.4:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL deionized water to obtain.
[0037] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.3 The Zn-LDH precursor was calcined in air at 500 °C for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.4 Zn-A-500.
[0038] (2)Mg2Zr 0.4 Catalytic effect test of Zn-A-500: Propylene carbonate and methanol were added into the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.4 Zn-A-500, heated to 70℃ and kept warm for 4h. After the reaction, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 94.67%. After separation, washing and drying, the catalyst was used again as the catalyst of the new reaction system. The catalyst was recovered by filtration and reused. After testing Mg2Zr 0.4 The secondary utilization dimethyl carbonate yield of Zn-A-500 is 87.49%, and the tertiary utilization dimethyl carbonate yield is 29.33%.
[0039] Embodiment 3:
[0040] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.5:1 was prepared by coprecipitation. 0.5 Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.5:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL deionized water to obtain.
[0041] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.5The Zn-LDH precursor was calcined in air at 500 °C for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.5 Zn-A-500.
[0042] (2)Mg2Zr 0.5 Catalytic effect test of Zn-A-500: Propylene carbonate and methanol were added into the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.5 Zn-A-500 was heated to 70°C and kept warm for 4 hours. After the reaction was completed, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 93.74%. After separation, washing and drying, the catalyst was used again as a catalyst in the new reaction system. The catalyst was recovered by filtration and reused. After testing Mg2Zr 0.5 The secondary utilization dimethyl carbonate yield of Zn-A-500 is 87.65%, and the tertiary utilization dimethyl carbonate yield is 69.14%.
[0043] Embodiment 4:
[0044] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.4:1 was prepared by coprecipitation. 0.4 Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.4:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL of deionized water to obtain.
[0045] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.4 The Zn-LDH precursor was calcined in air at 600 °C for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.4 Zn-A-600.
[0046] (2)Mg2Zr 0.4Zn-A-600 catalytic effect test: Propylene carbonate and methanol were added to the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.4 Zn-A-600, heated to 70℃ and kept warm for 4h. After the reaction, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 92.47%. After separation, washing and drying, the catalyst was used again as the catalyst of the new reaction system. The catalyst was recovered by filtration and reused. After testing Mg2Zr 0.4 The secondary utilization dimethyl carbonate yield of Zn-A-600 was 58.6%.
[0047] Embodiment 5:
[0048] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.4:1 was prepared by coprecipitation. 0.4 Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.4:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL of deionized water to obtain.
[0049] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.4 The Zn-LDH precursor was calcined in air at 700 °C for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.4 Zn-A-700.
[0050] (2)Mg2Zr 0.4 Zn-A-700 catalytic effect test: Propylene carbonate and methanol were added to the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.4Zn-A-700 was heated to 70°C and kept warm for 4 hours. After the reaction was completed, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 93.46%. After separation, washing and drying, the catalyst was used again as a catalyst in the new reaction system. The catalyst was recovered by filtration and reused. After testing Mg2Zr 0.4 The secondary utilization dimethyl carbonate yield of Zn-A-700 was 59.4%.
[0051] Embodiment 6:
[0052] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.4:1 was prepared by coprecipitation. 0.4 Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.4:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL deionized water to obtain.
[0053] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.4 The Zn-LDH precursor was calcined in air at 900 °C for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.4 Zn-A-900.
[0054] (2)Mg2Zr 0.4 Test of Zn-A-900 catalytic effect: Propylene carbonate and methanol were added into the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.4 Zn-A-900 was heated to 70°C and kept warm for 4 hours. After the reaction was completed, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 77.69%.
[0055] Embodiment 7:
[0056] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.4:1 was prepared by coprecipitation. 0.4Zn-LDH precursor. Solution A is Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.4:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL deionized water to obtain.
[0057] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.4 The Zn-LDH precursor was calcined at 500 °C in a nitrogen atmosphere for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.4 Zn-N-500.
[0058] (2)Mg2Zr 0.4 Zn-N-500 catalytic effect test: Propylene carbonate and methanol were added to the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.4 Zn-N-500, heated to 70℃ and kept warm for 4h. After the reaction, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 83.47%. After separation, washing and drying, the catalyst was used again as the catalyst of the new reaction system. The catalyst was recovered by filtration and reused. After testing Mg2Zr 0.4 The secondary utilization dimethyl carbonate yield of Zn-N-500 is 56.36%. The nitrogen effect here is not as good as the air in Example 3. It is speculated that the reason may be that the carbon structure of the material is retained by calcining in nitrogen, while carbon dioxide is formed by calcining in air, which has a certain pore-forming effect and forms a larger specific surface area. In addition, the primary calcination in air fully reacts with oxygen to completely form oxides, while oxides cannot be completely formed in a nitrogen atmosphere.
[0059] Embodiment 8:
[0060] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.4:1 was prepared by coprecipitation. 0.4Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.4:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL deionized water to obtain.
[0061] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.4 The Zn-LDH precursor was calcined at 600 °C in a nitrogen atmosphere for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.4 Zn-N-600.
[0062] (2)Mg2Zr 0.4 Test of Zn-N-600 catalytic effect: Propylene carbonate and methanol were added into the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.4 Zn-N-600, heated to 70℃ and kept warm for 4h. After the reaction, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 82.37%. After separation, washing and drying, the catalyst was used again as the catalyst of the new reaction system. The catalyst was recovered by filtration and reused. After testing Mg2Zr 0.4 The secondary utilization dimethyl carbonate yield of Zn-N-600 is 63.44%. In this embodiment, the primary utilization of nitrogen is worse than that of air, and the secondary utilization is better than that of air at the same temperature. The reason may be that the product of primary calcination in nitrogen atmosphere may not be completely formed into oxides, but it is slowly oxidized by contact with air during primary utilization and storage.
[0063] Embodiment 9:
[0064] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.4:1 was prepared by coprecipitation. 0.4 Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.4:1 ([Mg 2+ ]+[Al3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL deionized water to obtain.
[0065] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.4 The Zn-LDH precursor was calcined at 700 °C in a nitrogen atmosphere for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.4 Zn-N-700.
[0066] (2)Mg2Zr 0.4 Catalytic effect test of Zn-N-700: Propylene carbonate and methanol were added into the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.4 Zn-N-700, heated to 70℃ and kept warm for 4h. After the reaction, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 83.24%. After separation, washing and drying, the catalyst was used again as a catalyst in the new reaction system. The catalyst was recovered by filtration and reused. After testing Mg2Zr 0.4 The secondary utilization dimethyl carbonate yield of Zn-N-700 was 58.71%.
[0067] Embodiment 10:
[0068] (1) Mg2Zr with a Mg:Zr:Zn molar ratio of 2:0.4:1 was prepared by coprecipitation. 0.4 Zn-LDH precursor. Solution A is a mixture of Mg(NO3)2·6H2O, ZrO(NO3)2·xH2O, and Zn(NO3)2·6H2O in a molar ratio of Mg:Zr:Zn of 2:0.4:1 ([Mg 2+ ]+[Al 3+ ]+[Zr 4+ ]=0.05mol / L) was dissolved in 100mL of deionized water to obtain.
[0069] Solution B was a mixture of NaOH (2 mol / L) and Na2CO3 (0.3 mol / L) in deionized water (100 mL). Solution B was added dropwise to solution A with vigorous stirring until pH = 10. The resulting slurry was heated at 110 °C for 12 h. The resulting precipitate was separated, washed thoroughly with deionized water and ethanol, and dried at 60 °C for 24 h. Finally, the Mg2Zr 0.4 The Zn-LDH precursor was calcined at 900 °C in a nitrogen atmosphere for 4 h (heating rate 5 °C / min) to obtain a catalyst sample, denoted as Mg2Zr 0.4 Zn-N-900.Mg2Zr 0.4 Zn-N-900 and precursor Mg2Zr 0.4 The XRD pattern of Zn-LDH is shown in Figure 1 As shown, it can be seen that Mg2Zr 0.4 Zn-LDH undergoes a phase transition after calcination. Mg2Zr 0.4 Zn-N-900 is mainly composed of three crystal phases: MgO, ZrO2 and ZnO.
[0070] Mg2Zr 0.4 The SEM image of Zn-N-900 is as follows Figure 2 As shown, it can be seen that Mg2Zr 0.4 The surface of Zn-N-900 is a coral structure, which greatly increases the surface area of the material and improves the catalytic effect of the catalyst.
[0071] Mg2Zr 0.4 Zn-N-900 and Mg2Zr 0.4 The thermogravimetric curve of Zn-LDH in air atmosphere is shown in Figure 3 As shown in the figure, it can be seen that Mg2Zr 0.4 Zn-LDH undergoes structural collapse at around 300°C, but Mg2Zr 0.4 Zn-N-900 maintained a good structure throughout the test, proving that Mg2Zr 0.4 Zn-N-900 has good thermal stability.
[0072] (2)Mg2Zr 0.4 Zn-N-900 catalytic effect test: Propylene carbonate and methanol were added to the reactor at a molar ratio of 1:30, and the catalyst Mg2Zr was added at 1.5% of the total feed weight. 0.4Zn-N-900, heated to 70℃ and kept warm for 4h. After the reaction, the catalyst was recovered to obtain dimethyl carbonate and 1,2-propylene glycol. Gas chromatography analysis showed that the single-pass yield of dimethyl carbonate was 99.90%. After separation, washing and drying, the catalyst was used again as the catalyst of the new reaction system. The catalyst was recovered by filtration and reused. After testing Mg2Zr 0.4 The dimethyl carbonate yield of Zn-N-900 is 86.84% for the second utilization, 77.83% for the third utilization, 72.89% for the fourth utilization and 58.88% for the fifth utilization.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A multi-metal oxide derived from hydrotalcite, characterized in that: Mg2Zr is prepared by reacting zinc nitrate, magnesium nitrate and zirconium oxynitrate with sodium carbonate and sodium hydroxide. x Zn-LDH precursor; and then calcined to obtain, wherein x is 0.3 to 0.
5.
2. The method for synthesizing a multimetal oxide according to claim 1, characterized in that: The steps include: Step 1: Preparation of Mg2Zr x Zn-LDH precursor: Dissolve zinc nitrate, magnesium nitrate and zirconium oxynitrate in water to obtain solution A; add sodium carbonate solution and sodium hydroxide solution dropwise to solution A, stir vigorously, and control the pH of the mixed solution; heat the obtained slurry, separate the obtained precipitate Mg2Zr x Zn-LDH was washed with water and dried to obtain Mg2Zr x Zn-LDH precursor; Step 2: Synthesis of multi-metal composite oxides: Mg2Zr synthesized in step 1 x The Zn-LDH precursor is obtained by calcining at a certain heating rate to a specific temperature under a specific atmosphere.
3. The synthesis method according to claim 2, characterized in that In step 1, Zn 2+ Mg 2+ 、Zr 4+ The sum of the concentrations is 0~0.05mol / L.
4. The synthesis method according to claim 2, characterized in that In step 1, the zinc nitrate, magnesium nitrate and zirconium oxynitrate are salts or their respective hydrates.
5. The synthesis method according to claim 2, characterized in that In step 1, the obtained slurry is heated at 100-120° C. for 8-12 hours; and the precipitate is washed and dried.
6. The synthesis method according to claim 2, characterized in that In step 1, the concentration of the sodium hydroxide solution is 1-3 mol / L, and the concentration of the sodium carbonate solution is 0.2-0.5 mol / L.
7. The synthesis method according to claim 2, characterized in that In step 2, the calcination atmosphere should be an inert gas nitrogen atmosphere or an air atmosphere.
8. The synthesis method according to claim 2, characterized in that In step 2, the calcination temperature is 500-900°C.
9. The synthesis method according to claim 2, characterized in that: In step 2, the calcination heating rate is 2-5°C / min, and the calcination time is 2-4h.
10. Use of the multimetal oxide according to claim 1 in catalyzing the transesterification reaction of propylene carbonate and methanol.
